Seismic response of a stilted mid–story isolated structure in mountainous areas based on variable parameters soil–structure–interaction effect. (May 2023) - Wan, Feng; Zhou, Wangwang; Liu, Dewen; Huo, Yiran; Li, Hui; Luo, Xiaoxuan; Yao, Shunzhong
Abstract: Many mountainous areas in the world are vulnerable to earthquakes. The geology of mountainous areas is complicated, the terrain fluctuates wildly, and the dynamic characteristics differ from those of flat areas. The soil–structure-interaction (SSI) effect has rarely been considered in studies of mountain structures. Theoretical research on SSI in mountainous areas lags behind engineering applications. It is suggested that SSI should be considered in mountainous areas. In this study, three mountain structure models were established: a stilted mid–story isolated structure without SSI effect, a stilted mid–story isolated structure with traditional SSI effect and a stilted mid–story isolated structure with variable parameters SSI effect. The earthquakes were input in the direction of down and transverse slopes. The results indicate that the seismic response of the stilted mid–story structure with SSI effect is larger than that of the stilted mid–story structure without SSI effect in mountainous areas. The seismic response of the stilted mid–story structure with variable parameters SSI effect in mountainous areas is more accurate and reliable. The seismic response is significantly affected by the changes of soil stiffness and damping. The maximum stress values of the three structures appear at the stilted short columns and the ends of the connected beams. As the soil softens, the seismic response of the stilted mid–story isolated structure with SSI effect in mountainous areas increases. When earthquakes are input in the transverse slope direction, the soil twists, aggravating structural torsion.